2021
DOI: 10.3389/fpls.2020.570418
|View full text |Cite
|
Sign up to set email alerts
|

Histology and RNA Sequencing Provide Insights Into Fusarium Head Blight Resistance in AAC Tenacious

Abstract: Fusarium head blight (FHB) is a serious fungal disease affecting wheat and other cereals worldwide. This fungus causes severe yield and quality losses from a reduction in grain quality and contamination of grain with mycotoxins. Intensive breeding efforts led to the release of AAC Tenacious, which was the first spring wheat cultivar registered in Canada with a resistant (R) rating to FHB. To elucidate the physiological mechanisms of resistance, we performed histological and transcriptomic analyses of AAC Tenac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 46 publications
3
16
0
Order By: Relevance
“…The defence response of the same resistant plants induced at 4 dpi was characterised by a significantly more complex interplay between finely tuned and correlated metabolic pathways (Figure 12), clearly highlighting that several metabolic routes are associated with the FHB resistance conferred by the Fhb7E locus. This is in agreement with reports on rachis metabolic and transcriptomic analyses of other loci conferring FHB resistance to durum and bread wheat, including Fhb1 and Fhb2 of the Sumai 3 derivation [26,27,51], genes/QTL from Canadian bread and durum wheat germplasm [24,53] and the same Th. elongatum Fhb7E locus considered in the present work [69,70].…”
Section: Induced Response Of Fhb7e-carrier Lines To Fg Infection 421 ...supporting
confidence: 93%
See 1 more Smart Citation
“…The defence response of the same resistant plants induced at 4 dpi was characterised by a significantly more complex interplay between finely tuned and correlated metabolic pathways (Figure 12), clearly highlighting that several metabolic routes are associated with the FHB resistance conferred by the Fhb7E locus. This is in agreement with reports on rachis metabolic and transcriptomic analyses of other loci conferring FHB resistance to durum and bread wheat, including Fhb1 and Fhb2 of the Sumai 3 derivation [26,27,51], genes/QTL from Canadian bread and durum wheat germplasm [24,53] and the same Th. elongatum Fhb7E locus considered in the present work [69,70].…”
Section: Induced Response Of Fhb7e-carrier Lines To Fg Infection 421 ...supporting
confidence: 93%
“…Mycotoxins, of which the most commonly detected in FHB-affected wheat is deoxynivalenol (DON), are virulence factors that Fusarium pathogens produce, which, after floral invasion and hyphal spreading, reach the rachis node. Consistent evidence (e.g., [ 23 , 24 ] and references therein) indicates this spike section, together with the rachilla [ 25 ], as crucial for subsequent spike colonization by the fungus. It is at this level, in fact, that a main switch between a susceptible and a resistant host response occurs.…”
Section: Introductionmentioning
confidence: 63%
“…For example, transcinnamate 4-monooxygenase, a CYP450 involved in the pathway of lignin biosynthesis, catalyzes the oxidative reaction of trans-cinnamic acid to p-coumaric acid [136]. Several other studies have reported that CYP450s were expressed during FHB infection [69,133,137,138]. However, transcripts of one CYP450 gene accumulated only in resistant wheats and not in susceptible ones in response to F. graminearum compared to water controls [139].…”
Section: Mycotoxin Detoxificationmentioning
confidence: 99%
“…RNA-seq data from AAC Tenacious and Roblin generated by Kirby et al (2020) [54] were downloaded from NCBI. AAC Tenacious is the only spring wheat cultivar in Canada to receive a resistant rating to FHB, and belongs to the Canada Prairie Spring Red market class.…”
Section: Rna-seq Data and Analysismentioning
confidence: 99%